Domestic violence and depression among married women: an example of Malatya - Gülpınar, Serdar; Güneş, Gülsen (Scientific Reports in Medicine, 2025)
Objective: This study aimed to determine the prevalence and types of domestic violence among married women in Malatya, Türkiye, examine associated sociodemographic and partner-related factors, and assess the relationship with depression.Method: A cross-sectional study was conducted with 398 married women aged 15–49 registered at a Family Health Center between January and April 2019. Data were collected through face-to-face interviews using a questionnaire including sociodemographic data, the Domestic Violence Scale, and the Beck Depression Inventory. As data distribution was not normal, non-parametric tests (including Kruskal-Wallis with Bonferroni post-hoc correction) and Spearman correlation were applied, with p